Regulatory standards and processes for over-the-counter availability of hormonal contraception and drugs for medical abortion in five countries in the Eastern Mediterranean Region - Anne Ammerdorffer; Mark Laws; Arinze Awiligwe; Florence Erb; Wallada Im-Amornphong; A. Metin Gülmezoglu; Lester Chinery; Briana Lucido; Manjulaa Narasimhan (BMC, 2021)
Abstract The World Health Organization 2019 WHO consolidated guideline on self-care interventions for health: sexual and reproductive health and rights includes recommendations on self-administration of injectable contraception, over-the-counter (OTC) oral contraception and self-management of medical abortion. A review of the regulatory status of these two self-care interventions can highlight processes required to ensure that the quality of the medicines and safety of individuals are safeguarded in the introduction and scale-up in countries. This review outlines the legal regulatory status of prescription-only medicine (POM) and OTC contraceptives, including emergency contraception, and drugs for medical abortion in Egypt, Jordan, Lebanon, Morocco and Tunisia using information obtained from internet searches, regulatory information databases and personal contacts. In addition, the review examines whether the national medicines regulatory authorities have documented procedures available to allow for a change in status from a POM to OTC to allow for increased accessibility, availability and uptake of self-care interventions recommended by WHO. Egypt, Jordan and Lebanon have a documented national OTC list available. The only contraceptive product mentioned in the OTC lists across all five countries is ellaOne (ulipristal acetate for emergency contraception), which is publicly registered in Lebanon. None of the five countries has an official documented procedure to apply for the change of POM to OTC. Informal procedures exist, such as the ability to apply to the national medicines regulatory authority for OTC status if the product has OTC status in the original country of manufacture. However, many of these procedures are not officially documented, highlighting the need for establishing sound, affordable and effective regulation of medical products as an important part of health system strengthening. From a public health perspective, it would be advantageous for licensed products to be available OTC. This is particularly the case for settings where the health system is under-resourced or over-stretched due to health emergencies. Readiness of national regulatory guidelines and OTC procedures could lead to increased access, availability and usage of essential self-care interventions for sexual and reproductive health and rights.